The influence of lipoprotein(a) on fibrinolytic activity (Medical Journal of Indonesia, 2004)
Lipoprotein(a) is a plasma lipoprotein whose structure and composition are similar with low density lipoprotein (LDL) with an addition of apo(a) that is bound to apo B100. The structure of apo(a) is similar with plasminogen, a proenzym in fibrinolytic system. Due to this similarity, it is assumed that Lp(a) can inhibit plasminogen activity and decreases fibrinolytic activity. The purpose of this study is to prove that addition of Lp(a) to normal plasma can inhibit fibrinolytic activity. Four healthy people whose fibrinogen levels, plasminogen activities and euglobulin clot lysis time were within normal range were enrolled in this study. Fibrinolytic activity were assessed by euglobulin clot lysis time (ECLT). In the first experiment, the addition of Lp(a) was done before centrifugation to obtain euglobulin precipitates, while in the second experiment, Lp(a) was added to the euglobulin precipitates. As a control, ECLT was performed in the plasma with the addition of NaCl 0.9% in the same volume with Lp(a). The results of the study showed that in the first experiment, there was no clot formation. It is assumed that Lp(a) can bind fibrinogen and both of them floated in the supernatant, so there was no fibrinogen in the euglobulin precipitate that can be clotted by thrombin. In the second experiment, the clot did not dissolve until the fourth day. In conclusion, the addition of Lp(a) to normal plasma can inhibit the activity of fibrinolytic system. (Med J Indones 2004; 13: 135-9) Keywords: plasminogen, fibrinogen, apo(a), euglobulin clot lysis time (ECLT)